Fabrication of 3 D Mesoporous Black TiO2/MoS2/TiO2 Nanosheets for Visible‐Light‐Driven Photocatalysis. Issue 10 (25th April 2016) - Liu, Xuefeng; Xing, Zipeng; Zhang, Hang; Wang, Wenmei; Zhang, Yan; Li, Zhenzi; Wu, Xiaoyan; Yu, Xiujuan; Zhou, Wei
Abstract: A novel 3 D mesoporous black TiO2 (MBT)/MoS2 /MBT sandwich‐like nanosheet was successfully fabricated using a facile mechanochemical process combined with an in situ solid‐state chemical reduction approach, followed by mild calcination (350 °C) under an argon atmosphere. The MBT/MoS2 /MBT exhibits a 3 D sandwich‐like nanosheet structure and heterojunctions are formed at the interfaces between MoS2 and black TiO2 . The significantly narrowed band gap of MBT/MoS2 /MBT is attributed to the introduction of MoS2 and the formed Ti 3+ species in the frameworks. The visible‐light photocatalytic degradation rate of methyl orange and the hydrogen production rate are as high as 89.86 % and 0.56 mmol h −1 g −1, respectively. The introduction of MoS2 and Ti 3+ in the frameworks favors the visible‐light absorption and the separation of photogenerated charges, and the 3 D sandwich‐like heterojunction structure facilitates the transfer of photogenerated charges. Abstract : Pass the Mo : A 3 D sandwich of mesoporous black TiO2 (MBT)/MoS2 /MBT was fabricated using a facile mechanochemistry method combined with an in situ solid‐state chemical reduction approach. The material exhibited excellent visible‐light‐driven photocatalytic performance for pollutant degradation and hydrogen evolution owing to the sandwich‐like heterojunction structure and Ti 3+ doping.